Extensions of LINMAP model for multi criteria decision making with grey numbers - Hajiagha, Seyed Hossein Razavi; Hashemi, Shide Sadat; Zavadskas, Edmundas Kazimieras; Akrami, Hadi (Technological and Economic Development of Economy, 2012)
The linear programming technique for multidimensional analysis of preference, known as LINMAP is one of the existing well-known ideal seeking methods for multi attribute decision making problems. This method originally is proposed under crisp and deterministic circumstances. However, uncertainty is an indubitable property of decision making problems. In this paper, a new version of LINMAP-G is proposed where the decision maker’s judgments are expressed as grey numbers. Like original LINMAP method, the grey ideal solution and attributes weight vector is determined and alternatives are ranked according to their weighted distance from determined ideal point. Application of the proposed method is illustrated in two numerical examples.